Optimal Policy under Restricted Government Spending - Anders Sørensen (Copenhagen Business School (CBS), Department of Economics, 2006)
Welfare ranking of policy instruments is addressed in a two-sector Ramsey model with monopoly pricing in one sector as the only distortion. When government spending is restricted, i.e. when a government is unable or unwilling to finance the required costs for implementing the optimum policy, subsidies that directly affect investment incentives may generate higher welfare effects than the direct instrument, which is a production subsidy. The driving mechanism is that an investment subsidy may be more cost effective than the direct instrument; and that the relative welfare gain from cost effectiveness can exceed the welfare loss from introducing new distortions. Moreover, it is found that the investment subsidy is gradually phased out of the welfare maximizing policy, which may be a policy combining the two subsidies, when the level of government spending is increased.
hdl:10398/7581
Keywords: E61; O21; O41; 330; welfare ranking; indirect and direct policy instruments; restricted government spending